Exploring Current Development of Policy and Practice of Early Intervention Services in Taiwan - Yeh, CHIEN-TSO (Trinity College (Dublin, Ireland). School of Education, 2021)
Exploring Current Development of Policy and Practice of Early Intervention Services in Taiwan CHIEN-TSO, YEH In Taiwan the Early Intervention services have been developed for decades. However, during the long developmental process, relevant policy and legislation were considered as important bases to lead the implementation. This study aimed at gaining an understanding of present development of policy and practice of the Early Intervention in Taiwan and exploring how the two concepts, family-centred and professional team been executed in the field. Moreover, a comparison was made between Taiwan and other western countries in order to examine the current development of Taiwanese policy context. Apart from the documents and legislative context collected from Taiwanese government via different websites, a systematic search of relevant literature was conducted across both Taiwanese and international databases in this study. The method of document analysis was mainly adopted to examine the collected governmental documents. A series of current policy and implementation programme were found, and a discussion focused on the two concepts mentioned previously was presented. Key words: Early Intervention, policy, family-centred, professional team.
Keywords: Early Intervention; Education